Plot consolidation in sites and services projects: a case study of Bauchi project - Ahmed, Rukaiyatu Usman (1995)
This study sets out to find the reasons why the level of consolidation by the target beneficiaries of the World Bank assisted Sites and Services project in Makama Bauchi was low. The World Bank assisted Sites and Services strategy is one of the more recent public sector solutions to the low income housing problems adopted by many countries of the Developing World in the last two decades. The World Bank assisted Projects normally take two approaches: (1) Sites and Services where land is provided with physical infrastructure (e.g. roads, electricity and water supply) and community facilities (e.g. schools, health clinics), and divided into individual plots and allocated to specified target groups who are expected to build their houses through self-help, and live in them. (2) Settlement Upgrading where physical infrastructure is provided in an already existing settlement and land ownership are legalised where they were illegal, improvements of individual dwellings is expected to follow. With both approaches, the guiding principles are those of affordability, cost recovery and replicability.